2007
DOI: 10.1016/j.physbeh.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sleep, physical activity and human health

Abstract: Although sleep and exercise may seem to be mediated by completely different physiological mechanisms, there is growing evidence for clinically important relationships between these two behaviors. It is known that passive body heating facilitates the nocturnal sleep of healthy elderly people with insomnia. This finding supports the hypothesis that changes in body temperature trigger somnogenic brain areas to initiate sleep. Nevertheless, little is known about how the core and distal thermoregulatory responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
143
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(156 citation statements)
references
References 71 publications
5
143
3
5
Order By: Relevance
“…Lifestyle intervention programs for T2DM have been previously verified in many controlled trials: PA shows better effects on glycemic control and blood pressure than other therapies alone (12,13). Resistance training (14), isolated aerobic exercise, (15) and the combination of them (16) can improve glycemic adjustments; overall, the beneficial effects of exercise on physical fitness, disease symptoms, and quality of life in T2DM are strong (17)(18)(19)(20)(21). However, despite all these evidences, most patients remain sedentary (22,23).…”
Section: Introductionmentioning
confidence: 98%
“…Lifestyle intervention programs for T2DM have been previously verified in many controlled trials: PA shows better effects on glycemic control and blood pressure than other therapies alone (12,13). Resistance training (14), isolated aerobic exercise, (15) and the combination of them (16) can improve glycemic adjustments; overall, the beneficial effects of exercise on physical fitness, disease symptoms, and quality of life in T2DM are strong (17)(18)(19)(20)(21). However, despite all these evidences, most patients remain sedentary (22,23).…”
Section: Introductionmentioning
confidence: 98%
“…Insomnia is the most prevalent sleep disorder in the elderly (9) population and probably contributes to the overuse of medication to sleep, because this pharmacological method has been widely used to solve this problem (11,24) . Considering the undesirable effects of these drugs in the elderly, such fact has led to the search for non-pharmacological alternatives to improve the quality of sleep and reduce insomnia symptoms in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…Authors attribute the observed improvement to the fact that sleeping is a biological function directed at the conservation of energy and replacement of the everyday use of tissues, which is known to increase with physical activity practice (24) . This would reduce insomnia symptoms -early awakening, difficulty in initiating sleep and non-restorative sleep -that were found in between 20 and 30% of the elderly in this study, a high proportion, which deserves the attention of health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Despite applications of this evidence to medical treatment, few studies examine use of behavioral risk factors related to morning onset of cardiac events. For example, final decisions based on evidence regarding the safest time to exercise during the day are still pending (Atkinson et al, 2006;Atkinson & Davenne, 2007;Murray et al,1993;Shiotani et al, 2009;White, 2003).…”
Section: Introductionmentioning
confidence: 99%